Validation of Sience, Technology, Engineering, and Matemathic Based Diagnostik Assessment on Natural Resource Material for Phase B Elementary School Students using Rasch Model - Jihan Nadhifa Dewi; Siti Patonah*; Sukamto Sukamto (Jurnal Pendidikan Sains Indonesia, 2023)
One of the ways to design learning the implementation of the independent curriculum is assessment diagnostic. This study aims to develop STEM-based questions to measure students' critical thinking skills. The questions are used for the initial assessment of science subject material "Natural Resources" phase B elementary school. The type of research used is research and development (RD) with the ADDIE development model, consisting of the analysis, design, developmen, implementation, and evaluation stages. The school students in the city of Semarang with a total of 258 students consisting of 126 male students and 132 female students, using convenience sampling. The items' validation and reliability analysis techniques used the Aiken index and the RASCH model. The results showed that all items had a high validity category based on the following aspects: Outfit items, measure, test difficulty level, person and item reliability. There  are several phase bias items, where students in phase C benefit more than students in phase B. The average respon ability is above the averange item difficulty level. The conclusion is that the items developed can be used as initial assessments in science subjects